The effect of pore diameter on neo-tissue formation in electrospun biodegradable tissue-engineered arterial grafts in a large animal model. (1st October 2020) - Matsuzaki, Yuichi; Iwaki, Ryuma; Reinhardt, James W.; Chang, Yu-Chun; Miyamoto, Shinka; Kelly, John; Zbinden, Jacob; Blum, Kevin; Mirhaidari, Gabriel; Ulziibayar, Anudari; Shoji, Toshihiro; Breuer, Christopher K.; et al.
Abstract: To date, there has been little investigation of biodegradable tissue engineered arterial grafts (TEAG) using clinically relevant large animal models. The purpose of this study is to explore how pore size of electrospun scaffolds can be used to balance neoarterial tissue formation with graft structural integrity under arterial environmental conditions throughout the remodeling process. TEAGs were created with an outer poly-ε-caprolactone (PCL) electrospun layer and an inner sponge layer composed of heparin conjugated 50:50 poly (l-lactide-co-ε-caprolactone) copolymer (PLCL). Outer electrospun layers were created with four different pore diameters (4, 7, 10, and 15 µm). Fourteen adult female sheep underwent bilateral carotid artery interposition grafting ( n = 3–4 /group). Our heparin-eluting TEAG was implanted on one side ( n = 14) and ePTFE graft ( n = 3) or non-heparin-eluting TEAG ( n = 5) on the other side. Twelve of the fourteen animals survived to the designated endpoint at 8 weeks, and one animal with 4 µm pore diameter graft was followed to 1 year. All heparin-eluting TEAGs were patent, but those with pore diameters larger than 4 µm began to dilate at week 4. Only scaffolds with a pore diameter of 4 µm resisted dilation and could do so for up to 1 year. At 8 weeks, the 10 µm pore graft had the highest density of cells in the electrospun layer and macrophages were the primary cell type present. This study highlights challenges in designing bioabsorbable TEAGs for the arterial environment in a large animal model. While larger pore diameter TEAGs promoted cell infiltration, neotissue could not regenerate rapidly enough to provide sufficient mechanical strength required to resist dilation. Future studies will be focused on evaluating a smaller pore design to better understand long-term remodeling and determine feasibility for clinical use. Statement of Significance: In situ vascular tissue engineering relies on a biodegradable scaffold that encourages tissue regeneration and maintains mechanical integrity until the neotissue can bear the load. Species-specific differences in tissue regeneration and larger mechanical forces often result in graft failure when scaling up from small to large animal models. This study utilizes a slow-degrading electrospun PCL sheath to reinforce a tissue engineered arterials graft. Pore size, a property critical to tissue regeneration, was controlled by changing PCL fiber diameter and the resulting effects of these properties on neotissue formation and graft durability was evaluated. This study is among few to report the effect of pore size on vascular neotissue formation in a large animal arterial model and also demonstrate robust neotissue formation. Graphical abstract: Image, graphical abstract